Retrieval of a fractured instrument using File Braiding technique: A case report - Uddin, Md Farid; Alam, Md Samsul; Howlader, Md Mujibur Rahman; Moral, Ali Azgor (Update Dental College Journal, 2013)
In the present study, a conservative approach for removal of a fractured instrument located at the apical root area of maxillary left central incisor of a 35 years old male was performed and the clinical outcome was evaluated. On clinical examination, localized swelling associated with discharge of pus was seen near to the affected tooth. Furthermore, the tooth was restored with temporary filling and it was severely discolored. On radiographic examination, a radiolucent area around the apex was seen and there was a fractured instrument at the apex of the tooth. Tooth was then treated as nonsurgical endodontic technique and an attempt to remove the fractured instrument was undertaken. The results confirms that fractured instrument was successfully removed by using the File Braiding technique and after 3 months follow up, the tooth was asymptomatic and radiograph shows complete healing of the periapical lesion. DOI: http://dx.doi.org/10.3329/updcj.v2i1.13957 Update Dent. Coll. j: 2012; 2 (1): 25-30